2011
DOI: 10.1007/s00449-011-0655-3
|View full text |Cite
|
Sign up to set email alerts
|

The synergistic effect on production of lignin-modifying enzymes through submerged co-cultivation of Phlebia radiata, Dichomitus squalens and Ceriporiopsis subvermispora using agricultural residues

Abstract: The lignin-modifying enzymes (LMEs) play an important role in decomposition of agricultural residues, which contain a certain amount of lignin. In this study, the production of LMEs by three co-cultivated combinations of Phlebia radiata, Dichomitus squalens and Ceriporiopsis subvermispora and the respective monocultures was comparatively investigated. Laccase and manganese peroxidases (MnP) were significantly promoted in the co-culture of P. radiata and D. squalens, and corncob was verified to be beneficial fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 35 publications
(31 reference statements)
1
14
0
Order By: Relevance
“…In addition, noticeable toxicity reduction of the treated solutions was also successfully detected. The nature of this enhancement is not yet fully understood; the induction of different laccase isoenzymes has already been reported in other fungal systems such as Phlebia radiata/Dichomitus squalens (Dong et al, 2012), other works (e.g. He et al, 2010) have found an equivalent Table 2 Laccase and MnP activities (U g À1 ± SD) of wasted solid media after 14 days of undisturbed growth plus 14 days after processing and mixing.…”
Section: Discussionmentioning
confidence: 87%
“…In addition, noticeable toxicity reduction of the treated solutions was also successfully detected. The nature of this enhancement is not yet fully understood; the induction of different laccase isoenzymes has already been reported in other fungal systems such as Phlebia radiata/Dichomitus squalens (Dong et al, 2012), other works (e.g. He et al, 2010) have found an equivalent Table 2 Laccase and MnP activities (U g À1 ± SD) of wasted solid media after 14 days of undisturbed growth plus 14 days after processing and mixing.…”
Section: Discussionmentioning
confidence: 87%
“…Examples of co-cultures of more diverse populations include cultures of cells from different species of multicellular eukaryotic organisms [77][78][79][80][81][82][83], fungi [84] or different bacterial species [10,18,22,34,55,85,86]. Mammalian and bacterial cells have been co-cultured, either for infection studies [1,87,88] or testing of synthetic bacteria [35,36,89].…”
Section: Large Differences Between Cultured Populations Enabled By Sementioning
confidence: 99%
“…B i o c o n v e r s i o n o f l i g n o c e l l u l o s i c biomass into its components has a major importance for recycling of the carbon fixed by photosynthesis. Most of the natural degradation processes occur by the combination of enzyme mixtures and metabolic pathways of several microorganisms (Hu et al, 2011;Dong et al, 2012). Therefore, co-culture of different microorganism culture may result in production of the preferred enzymes more efficiently than their monocultures (Hu et al, 2011).…”
Section: Resultsmentioning
confidence: 99%
“…By far, several reports have been released to fungal coculturing to increase production of the enzymes involving in lignocellulose degradation. Although there are several reports for cellulase (Vinogradova and Kushnir, 2003;Hu et al, 2011;Singh et al;, xylanase (Dwivedi et al, 2011;Hu et al, 2011;Singh et al; and LiP (Qi-he et al, 2011;Dong et al, 2012), majority of the attempts to increase laccase (Hailei et al, 2009(Hailei et al, , 2013Flores et al, 2010;Hiscox et al, 2010;Hu et al, 2011;Qi-he et al, 2011;Dwivedi et al, 2011;Dong et al, 2012;Cupul et al, 2014;Kuhar et al, 2015;Wang et al, 2015;Singh et al;. On the other hand, Cupul et al, (2014) reported that induction of MnP production in coculture conditions has been paid relatively little attention.…”
Section: Resultsmentioning
confidence: 99%